Scientific evidence for the use of "serious games" or therapeutic games in people with Alzheimer’s Disease and other dementias - Redolat, Rosa; Mercedes Fernandez-Rios; Nuria Martinez; Ana Moron; Soledad Corachan (Technium Social Sciences Journal, 2020)
The progressive ageing of the population, together with the increase in the prevalence of neurodegenerative diseases and the lack of effective pharmacological treatments for Alzheimer’s disease (AD) raises the need to seek new therapeutic perspectives. It has been proposed that technology can provide integrated solutions in different areas related to the health and well-being of the patients. In recent years there has been growing interest in the so-called "serious games" or "therapeutic games" aimed at diagnosis or cognitive training in people with Mild Cognitive Impairment (MCI) or AD. The aim of this work is to review the scientific evidence that supports the application of "serious games" in the field of dementia. It presents the concept of "serious games" as well as the objectives and main recommendations in the development of this type of therapeutic games aimed at people with MCI or dementia. It also describes some examples of the implementation of serious games through Information and Communication Technologies. The main benefits and limitations arising from the application of these games in people with dementia are also exposed. We conclude future directions of research aiming to better interventions.